Qualidade de vida, funcionalidade e morbidade referida : avaliação em idosos na atenção básica de saúde - Mata, Adala Nayana de Sousa (2011)
Demographic and epidemiological transformations have led to an increase in elderly populations in the world, and chronic diseases become the main health problem in this population, with consequences for the independence and autonomy, and interfering in the lifestyle and daily activities, and may decrease the welfare and quality of life. So, there is an urgent need for multidisciplinary research on the quality of life, understood as a multidimensional and subjective concept, as well as the associated factors, such as health habits, presence of chronic conditions and functional capacity. Thus, In qualitative terms, the Article 1 provides an assessment and perception of the elderly about their quality of life. Article 2, in turn, presents the results of more extensive quantitative research, which can be seen that age, presence of chronic diseases and depression were associated with the quality of life. Thus, we discuss the need for action was planning and health strategies, with interdisciplinary approach, considering the environmental context and reality of family elders, promoting quality in the process of aging